Porcine or Bovine Tissue Valves: Which are Better for Surgical Aortic Valve Replacement? - Georgi Manchev; Valya Goranovska; Georgi Stoitsev; Boyan Markov; Vassil Gegouskov (Journal of Biomedical & Clinical Research)
The choice between mechanical and bioprosthetic aortic valve implants is affected by relatively clear criteria. However, the choice between porcine or pericardial valve is more complex regarding bioprosthetic devices. We aimed to elucidate any hemodynamic and clinical difference between two widely used bioprosthetic valves: the Sorin Mitroflow bovine pericardial valve and the St. Jude Medical Epic Supra porcine valve. We retrospectively studied 71 consecutive patients separated into two groups based on the valve they received. Clinical outcomes included patient survival and hemodynamic performance of the implanted prostheses. Patients were assessed at one and five years postoperatively. Mean transprosthetic pressure gradients were used as a marker of hemodynamic performance. The Mitroflow valve exhibited lesser mean transvalvular gradients than the Epic valve for all labelled sizes at one and five years postoperatively. The 5-year survival was equal between groups. Both prostheses demonstrated a small but significant increase in mean pressure gradients in the fifth year. Most patients enjoyed significant clinical improvement as assessed by NYHA functional class. Both bioprostheses performed very well with excellent hemodynamic parameters. The pericardial valves are a safe and appropriate choice for surgical bioprosthetic aortic valve replacement.